Kepemimpinan Kepala Sekolah Menengah Atas Negeri 1 Indralaya Kecamatan Indralaya Kabupaten Ogan Ilir - Desy Lestari (UNISAN JURNAL, 2024)
This research aims to analyze the leadership practices of the Principal of State High School 1 Indralaya, with a focus on effectiveness, leadership style, and its impact on the school environment. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with principals, teachers, school staff and students, as well as direct observations in the school environment. The research results show that the Principal of State High School 1 Indralaya applies an effective transformational leadership style in managing the school. The Principal has good communication skills, is able to motivate staff, and provides clear direction to achieve the school’s vision. Apart from that, inclusive and collaborative leadership is also one of the Principal’s strengths in building a conducive school climate. The positive impact of this leadership is reflected in increased teacher performance and student achievement. However, research also identifies several challenges faced by school principals, such as managing limited resources and pressure from various parties related to education policy. In conclusion, the leadership of the Principal of State High School 1 Indralaya has a significant role in forming a dynamic and high-achieving school culture. The implication of this research is the need for continued support from related parties to strengthen the role of leadership in improving the quality of education in the school. Further research can be conducted to understand in more depth the factors that influence school leadership success in different contexts.